(untitled) (مجلة إحالات, 2026)
He is one of the most prominent pioneers of the intellectual and reformist renaissance in Algeria in the twentieth century. He is known for his significant role in resisting French colonialism, both culturally and religiously, by reviving the Islamic and Arab identity of the Algerian people. He called for adherence to Algeria’s Islamic and Arab identity, refusing assimilation into French culture. He worked tirelessly to establish the Association of Muslim Scholars.